Analysis of Implementation Time Performance Using Earned Value Method - Pontan, Darmawan; Daniel, Daniel; Pentagon, Pentagon; Manisha, Manisha; Sumeru, Indrawati (Journal La Multiapp, 2025)
Construction projects often face cost and time constraints, while projects are required to be completed on schedule. To overcome these problems, an accurate management system is needed in a construction project to measure time performance, which refers to the progress of the work. By applying the earned value management (EVM) method, it is possible to project progress and weekly performance indices, making it easier to evaluate when there are deviations from the schedule. This study aims to analyze schedule variations and weekly time productivity, enabling the prediction of when the project will be completed. In the construction project of the Faculty of Law Building at Samratulangi University in North Sulawesi Province, reviews were conducted in weeks 1, 5, 10, 11, 20, and 25, where each review period had different CV, SV, and CPI values, allowing to assess at which time the predicted time was closest to the actual time occurring on-site.